PENDAMPINGAN PROGRAM BELAJAR BERBASIS SMART HOME DI DESA RASAU - Tri Wiyoko; Ikhsan Maulana Putra; Ayu Ulan Sari; Murni Sartika (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Online learning that is applied in schools turns out to leave some problems for students. There are students who do not use their time to study at home, but are used to play outside the home. As a result, there are students who do not understand and are not unprepared for parents in guiding their children to study. This community service program is carried out in the village of Rasau. This service is carried out with the Smart Home concept. The methods used in this service include preparation, implementation and evaluation. The results of the assistance service for smart home-based learning programs are carried out by providing assistance in learning to read, write, count and learn foreign languages. Furthermore, providing vocational training to train psychomotor abilities and physical fitness assistance to maintain the physical health of students. So learning assistance provides benefits for improving cognitive and psychomotor students in the village of Rasau.